Planning and decision making - Smith, Jane (BTEC HNC/HND business studies., 1996)
Planning and Decsion Making helps students to understand the relationships between corporate, functional and individual plans and objectives. It provides a framework for business planning and decision making and for contingency planning when dealing with risk.